A Juridical Analysis of Advocates’ Obligation to Provide Pro Bono Legal Aid under Indonesian Law Number 16 of 2011 on Legal Aid - Febranto Pratana Siahaan; Poltak Siringo-ringo; Marudut Silitonga (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The provision of legal aid by advocates has not yet been fully regarded as part of social contribution and social responsibility. The obligation of advocates to provide pro bono legal aid is closely connected to the concept of the rule of law and the law enforcement system that reflects the legal ideals or rechtsidee, namely legal certainty (rechtsicherheit), justice (gerechtigkeit), and utility (zweckmässigkeit). The research problems in this thesis are: first, how is pro bono legal aid by advocates regulated under the prevailing laws and regulations? Second, what are the urgency and obstacles in the implementation of pro bono legal aid by advocates, and what efforts can be made to overcome them?. This study uses normative or doctrinal legal research. The research approaches applied are the statutory approach and the conceptual approach. The research data consist of secondary data, analyzed using a qualitative method. The findings show that advocates’ interest in fulfilling their obligation to provide pro bono legal aid remains low. The provision of legal aid by advocates has not yet become part of their social contribution and social responsibility, despite the position of advocates as an officium nobile profession that carries the duty to provide free legal assistance. Furthermore, the obligation to report the implementation of pro bono legal aid by advocates has not been clearly and firmly regulated under the Advocate Law. This condition has hindered legal protection for poor and disadvantaged communities in accessing pro bono legal aid. Therefore, a standardized system and mechanism are needed regarding the reporting obligation for the provision of pro bono legal aid. The Advocate Law also needs to be revised, particularly concerning the obligation to provide pro bono legal aid and the supervision carried out by Advocates’ Organizations. Concrete strategic measures are also required to empower and strengthen the implementation of pro bono legal aid.